2012
DOI: 10.5492/wjccm.v1.i4.94
|View full text |Cite
|
Sign up to set email alerts
|

Infection control in severely burned patients

Abstract: In the last two decades, much progress has been made in the control of burn wound infection and nasocomial infections (NI) in severely burned patients. The continiually changing epidemiology is partially related to greater understanding of and improved techniques for burn patient management as well as effective hospital infection control measures. With the advent of antimicrobial chemotherapeutic agents, infection of the wound site is now not as common as, for example, urinary and blood stream infections. Univ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 40 publications
1
41
0
2
Order By: Relevance
“…Contaminated burning wards and duration of patients stay in hospital, in addition to the size of surface area of burned skin are the most important reasons to increase of persistent and multiplication of pathogenic bacteria in the burned areas 40 . There are a number of factors that influence the emergence of infection in burns patient including; prolonged hospital stays, contamination of burns wards, nature of burn injury itself, as well as intensive diagnostic and therapeutic procedures 41,42 . Some studies suggested that burn infection is the most common type of infection, while, others studies reports show it to be bacteremia and pneumonia 43,44 .…”
Section: Discussionmentioning
confidence: 99%
“…Contaminated burning wards and duration of patients stay in hospital, in addition to the size of surface area of burned skin are the most important reasons to increase of persistent and multiplication of pathogenic bacteria in the burned areas 40 . There are a number of factors that influence the emergence of infection in burns patient including; prolonged hospital stays, contamination of burns wards, nature of burn injury itself, as well as intensive diagnostic and therapeutic procedures 41,42 . Some studies suggested that burn infection is the most common type of infection, while, others studies reports show it to be bacteremia and pneumonia 43,44 .…”
Section: Discussionmentioning
confidence: 99%
“…However, diabetic patients did not have higher odds of mortality [29]. Early burn mortality is attributable to acute infections leading to sepsis, however early excision and grafting and the use of ICU protocols such as ventilator and sepsis bundles has led to the reduction of early sepsis associated burn mortality [30]. …”
Section: Discussionmentioning
confidence: 99%
“…It is more prevalent in susceptible patient populations, including immunosuppressed, cystic fibrosis, and burn patients 4 . With improvements in wound care and resuscitation, pneumonia is a major cause of morbidity and mortality in the burn patient population 1,5,6 . In particular, PA is the most frequently isolated bacterial pathogen 1,7 .…”
Section: Introductionmentioning
confidence: 99%